A comparison of different pretreatments on hydrogen fermentation from waste sludge by fluorescence excitation-emission matrix with regional integration analysis. (5th January 2015) - Guo, Liang; Lu, Mingmin; Li, Qianqian; Zhang, Jiawen; She, Zonglian
Abstract: To gain a better understanding of the influence on hydrogen fermentation with different pretreatments, the compositional and structural characteristics of extracellular polymeric substances (EPS) and dissolved organic matters (DOM) were analyzed during hydrogen fermentation using excitation-emission matrix (EEM) with fluorescence regional integration (FRI). In order to accelerate the hydrogen production with waste sludge, multi-enzyme, thermophilic bacteria, heat and microwave were performed for sludge pretreatments. The best method was found to be heating with the maximum hydrogen yield of 15.3 ml H2 /g VSS (Volatile suspended solid). EPS and DOM component of soluble chemical oxygen demand (SCOD), carbohydrate and protein, the microbial community structure evolutions, soluble metabolite of volatile fatty acids (VFAs) and ethanol distribution characteristics and pH were also evaluated. Different pretreatments could change the microbial community structure in waste sludge, which led to the diversity of substrates degradation and metabolite with hydrogen bacteria. Highlights: Hydrogen producing with different pretreated sludge was evaluated by EPS and DOM. Composition and structure character of EPS and DOM were analyzed by EEM with FRI. Heating was most efficient for sludge hydrogen production with waste sludge. Microbial community after pretreatments could affect hydrogen bacteria metabolite. EEM gain a better understanding of pretreatments on sludge hydrogen fermentation.